Errors and complications in hip arthroplasty using cement technology. - Loskutov, O. E.; Vasil’chenko, E. V. (Medicni Perspektivi, 2014)
According to the latest qualitative European registers cement type of fixation of one or both components of the hip joint is used in 4,5-58 % of cases, and in Scandinavian countries the figure is close to 90%. Performing any kind of surgery on musculoskeletal system surgeon should be prepared for post-operative complications. This study presents analysis of errors and complications of 65 hip replacements using cement technology. The technical errors of hip replacement with cement technologies usage are: the uneven distribution of the cement mantle around the endoprosthesis components, incomplete filling of the femoral medullary canal and bed of acetabular bone with cement, incorrect position of the implant components in the bone bed. The nature and number of somatic complications after total cemented replacement, observed in the group of patients that we investigated were: a transient drop in blood pressure − 11 (78.6 %) cases, thrombophlebitis − 1 (7.1%) case, transient coronary arteries ischemia − 1 (7.1%) case, cerebrovascular complications − 1 (7.1%) case.